Investigation of indentation size effect and R-curve behaviour of Li2O–SiO2 and Li2O–2SiO2 glass ceramics - Alao, Abdur-Rasheed; Azmir, Azhari (Elsevier Ltd., 2021)
Indentation size effect (ISE) and R-curve behaviour of Li2O–SiO2 and Li2O–2SiO2 glass ceramics are investigated using micro-indentation and indentation-strength (IS) techniques, respectively. Vickers micro-indentations were applied on both materials at the load of 0.10–19.6 N to determine the load influence on the measured hardness. For the IS-measured fracture toughness, the load ranged from 1.96 to 19.6 N. The hardness decreased with increasing load by 20% and 18% on Li2O–SiO2 and Li2O–2SiO2 glass ceramics, respectively, indicating the ISE behaviour on both materials. The fracture toughness increased with the load by 27% and 59% on Li2O–SiO2 and Li2O–2SiO2 glass ceramics, respectively, signifying the R-curve behaviour. The ISE behaviour of both materials was analysed using the Meyer's, Hays–Kendall (HK), proportional specimen resistance (PSR), Nix–Gao (NG), modified PSR (MPSR) and elastic plastic deformation (EPD) models while the R-curve behaviour was analysed by the fractional power law. The Meyer's index of both materials was less than 2, strongly confirming the ISE existence. The HK, PSR and NG models were only suitable to determine intrinsic Vickers hardness for Li2O–2SiO2 glass ceramic while the MPSR and EPD models were successful for both materials. The fractional power law gave higher R-curve steepness for Li2O–2SiO2 than Li2O–SiO2 glass ceramics. Also, material and brittleness indices predicted, respectively, higher quasi-plasticity and better machinability for Li2O–2SiO2 than Li2O–SiO2 glass ceramics indicating superior performance in the former to the latter. Finally, this study presents a new significant insight into the micro-mechanisms of fracture tolerance behaviour of these glass ceramics which is critical to their functional performance as structural ceramics.